Enhancing musical creativity through AI: a chain-mediation model of self-efficacy and emotional intelligence - Wang, Tingzheng; Zhang, Junhan (Frontiers in Psychology, 2025)
IntroductionThe rapid advancement of AI technology is fundamentally transforming traditional music creation and influencing music education. However, whether and how the use of AI genuinely enhances musical creativity remains a subject for further exploration. This study aims to investigate the impact of AI usage on the musical creativity of music majors.MethodsGrounded in the “zone of proximal development” and social cognitive theory, this study constructed a theoretical model. The model introduced “musical self-efficacy” and “musical emotional intelligence” as mediating variables to explore the role of individual psychological factors. A quantitative approach was employed, utilizing questionnaire surveys and structural equation modeling (SEM) to analyze the relationships.ResultsThe findings revealed that: (1) The use of AI had a significant positive impact on enhancing musical creativity. (2) Musical emotional intelligence mediated the relationship between AI use and creativity, suggesting that individuals with higher emotional intelligence could better leverage AI. (3) Musical self-efficacy also served as a mediator, indicating that one’s belief in their own abilities influenced the effectiveness of AI tool use. (4) Music self-efficacy and music emotional intelligence acted as sequential mediators, highlighting the important moderating role of psychological factors between technology and creativity.DiscussionThis study deepens the understanding of the relationship between AI technology and musical creativity. It provides practical guidance for higher music education, emphasizing the need to cultivate students’ self-efficacy and emotional intelligence in AI-assisted creative environments to achieve a synergistic development of technology and creativity.